Pembuatan Buku Saku Panduan Pemakaian Retinol untuk Mencegah Penuaan bagi Pemula (Jurnal Tata Rias, 2022)
One of phenomena has been realized by people that there are many individuals who have experienced the aging process prematurely. Retinol is one of the active ingredients that can treat skin problems, like skin aging, hyperpigmentation to acne problems. Along with the widespread use of retinol, there are some people who don’t understand that retinol is an active ingredient which in its use requires basic knowledge so that retinol works optimally and negative reactions at the beginning of use can be minimized. This study aims to create a pocket book that contains information about the active ingredient retinol, things to do before using retinol, as well as a guide to the use of retinol based on the product form. All of this information is made more interesting in a pocket book because it is packaged briefly, concisely, and clearly in language easily understood by beginners, or all people in various circles who want to use retinol ingredients. The stage of making this book consists of the analysis stage, the design stage, development stage and the implementation stage, the assessment of the book is carried out by two experts, media experts and material experts. The results of making this book meet the validation criteria with the results obtained by material experts is 79%, from media experts is 92%, so it can be concluded that the book is suitable to be used as a reference and guide to use retinol for beginners. Keywords: Pocket Book, Guide, Retinol, Skin Aging